Revisiting Jewson and Mason: The Politics of Gender Equality in UK Local Government in a Cold Climate. Issue 1 (30th June 2016) - Conley, Hazel; Page, Margaret
Abstract : This paper revisits Jewson and Mason's seminal theoretical framework on liberal and radical approaches to equal opportunity policy and practice by applying it to our research on the implementation of the Gender Equality Duty in UK local government. Conducted at the height of Thatcherism, Jewson and Mason's research offers a useful platform for assessing equality initiatives in local government during periods of political hostility to equality underpinned by cuts to public services, which in more recent time is ascribed to austerity. Drawing on qualitative research in five case study local authorities, this paper assesses strategies for protecting and promoting gender equality practices and policies in the face of change within public services. We analyse three types of politics of equality (political philosophy, organizational politics and party politics) that feature in Jewson and Mason's analysis. In line with recent feminist research, our data indicate that equality specialists continue to use both liberal and radical discourses in instrumental ways to promote equality and resist change as described by Jewson and Mason, but these were more clearly framed within business case arguments influenced by the modernization agenda of the 1990s. Our data indicate that even business case arguments have been unable to protect equality initiatives from the 2010 coalition government's austerity and cuts agenda.